Peningkatan Minat Belajar Melalui Metode Role Playing berbasis PBL pada Kurikulum Merdeka - Latifah, Nahdliatul; Munandar, Kukuh; Giri Prasetyo, Wahyu (JURNAL BIOSHELL, 2023)
Implementing learning in an independent curriculum gives teachers freedom in designing learning. Based on the results of observations and diagnostic tests carried out in class, this shows low interest. The PBL learning model using the role-playing method is believed to be able to increase interest in learning biology through fun activities and student involvement. This research includes classroom action research, which consists of planning, implementation, observation, and reflection stages in two cycles carried out in the 2022–2023 academic year in class XA of BPPT Darus Sholah Superior High School. Data on learning interest was obtained from observation sheets and closed questionnaires. The results of the research showed that there was an increase in the average score from cycle I to cycle II, namely from 67.93% to 77.12%, so that the PBL model using the role-playing method could increase students' interest in learning biology lessons.